دور تقييم الأداء المالي في تشخيص الوضعية المالية للمؤسسة الاقتصادية - غنية, قاسمية; مريم, عطية; هناء, العايب (University of eloued جامعة الوادي, 2021)
"يعبر تقييم الأداء المالي على إبراز مدى قدرة المؤسسة على تحقيق أهدافها المسطرة وذلك من خلال الاستغلال الأمثل لمواردها المالية المتاحة بكفاءة وفعالية، أي قياس النتائج المحققة أو المنتظرة اعتمادا على معايير محددة مسبقا وتقديم حكما على إدارة الموارد البشرية والمالية المتاحة للمؤسسة وهذا لخدمة أطراف مختلفة لها علاقة بالمؤسسة. ونهدف من خلال هذه الدراسة إلى إبراز دور تقييم الأداء المالي في تشخيص الوضعية المالية للمؤسسة الاقتصادية من خلال دراسة مؤشرات التوازن المالي والنسب المالية لتقييم الأداء المالي بالاعتماد على معلومات القوائم المالية. أما في الجانب التطبيقي فقد قمنا بإسقاط الدراسة على شركة روائح الورود بالوادي وذلك من خلال حساب مختلف نسب تقييم الأداء المالي التي تضمنتها القوائم المالية المقدمة لنا، وتشخيص الوضعية المالية للشركة على مدى أربع سنوات والمقارنة بينها. ""institution is able to achieve its set goals through the optimal use of its available financial resources efficiently and effectively, that means, measuring the achieved or expected results basing on pre-defined criteria and providing a judgment on the management of human and financial resources available to the institution and this is to serve Various parties involved in the organization. We aim through this study to highlight the role of financial performance evaluation in diagnosing the financial position of an economic institution by studying the indicators of financial balance and financial ratios to evaluate financial performance based on financial statements information. On the practical side, we dropped the study on the Rose Fragrances Company in El-Oued by calculating the various ratios of financial performance evaluation included in the financial statements presented to us, diagnosing the financial position of the company over four years and comparing them. Keywords: financial performance, financial performance évaluation, Financial position diagnosis, economic institution. "
مذكرة ماستر محاسبة
Keywords: الأداء المالي، تقييم الأداء المالي، تشخيص الوضعية المالية، المؤسسة الاقتصادية.; financial performance, financial performance évaluation, Financial position diagnosis, economic institution.